Evaluasi Penerapan Standar Operasional Prosedur (Sop) Pencegahan Dan Pengendalian Infeksi Pasien Di Unit Rawat Inap Bedah Rsud Dr. M.M Dunda Limboto - Ahmad, Putri; Efendy Tilome; Toar Hatibie (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This research aims to evaluate the implementation of Standard Operating Procedures (SOP) prevention and control of patient infections in the surgical inpatient unit of RSUD Dr. M.M Dunda Limboto, by using distributing questionnaires method (questionnaires) to medical and paramedical personnel. This research method uses descriptive research with a quantitative approach. The research was carried out on 20 respondents, namely medical and paramedical staff by distributing questionnaires containing 20 questions for each research subject. the aim is to explore deeply the application of Standard Operating Procedures (SOP) prevention and control of patient infections in the surgical inpatient unit at RSUD Dr. M.M DundaLimboto. The data in this research were analyzed univariately, univariate analysis is an analysis used on one research variable. The results showed that the Standard Operating Procedures (SOP) for prevention and control of patient infections in the Surgical inpatient unit of RSUD Dr. M.M DundaLimboto has been implemented by health workers with the percentage of the application being 85%.